Become a mother in times of pandemics: integrative literature review (Revista Contexto & Saúde, 2023)
The objective of this study was to know the publications on becoming a mother in the period of the Coronavirus Disease 2019 pandemic in the years 2020-2021, through an integrative review. Original articles that answered the guiding question, in Portuguese, English or Spanish, in the years 2020 and 2021, were included. The search for articles was performed in the following databases: Sage Journals, Online System for Search and Analysis of Medical Literature and Latin American and Caribbean Literature in Health Sciences. The final sample consisted of 12 articles, five articles in the Sage Journals database, six in the Online System for Search and Analysis of Medical Literature and one in Latin American and Caribbean Literature in Health Sciences. With this review it was observed that the COVID-19 pandemic affected pregnant and postpartum women, with a high rate of anxiety and depression.
Keywords: COVID-19; Infant, Newborn; Mother-Child Relations